Insight and Recommendations for Fragile X-Premutation-Associated Conditions from the Fifth International Conference on FMR1 Premutation - Flora Tassone; Dragana Protić; Emily G. Allen; Alison D. Archibald; Anna Baud; Ted W. Brown; Dejan B. Budimirovic; Jonathan Cohen; Brett D. Dufour; Rachel Eiges; Nicola Elvassore; Lidia V. Gabis; et al. (Cells, 2023)
gene is crucial for the accurate diagnosis, genetic counseling, and appropriate management of affected individuals and families. This paper summarizes all the known problems associated with the premutation and documents the presentations and discussions that occurred at the International Premutation Conference, which took place in New Zealand in 2023.
Keywords: Genetics and Neurodevelopmental Disorders